Expert perspectives on global biodiversity loss and its drivers and impacts on people. Issue 2 (18th July 2022) - Isbell, Forest; Balvanera, Patricia; Mori, Akira S; He, Jin‐Sheng; Bullock, James M; Regmi, Ganga Ram; Seabloom, Eric W; Ferrier, Simon; Sala, Osvaldo E; Guerrero‐Ramírez, Nathaly R; Tavella, Julia; Larkin, Daniel J; et al.
Abstract : Despite substantial progress in understanding global biodiversity loss, major taxonomic and geographic knowledge gaps remain. Decision makers often rely on expert judgement to fill knowledge gaps, but are rarely able to engage with sufficiently large and diverse groups of specialists. To improve understanding of the perspectives of thousands of biodiversity experts worldwide, we conducted a survey and asked experts to focus on the taxa and freshwater, terrestrial, or marine ecosystem with which they are most familiar. We found several points of overwhelming consensus (for instance, multiple drivers of biodiversity loss interact synergistically) and important demographic and geographic differences in specialists' perspectives and estimates. Experts from groups that are underrepresented in biodiversity science, including women and those from the Global South, recommended different priorities for conservation solutions, with less emphasis on acquiring new protected areas, and provided higher estimates of biodiversity loss and its impacts. This may in part be because they disproportionately study the most highly threatened taxa and habitats. Front Ecol Environ 2022;